1995
DOI: 10.1111/j.1464-410x.1995.tb07675.x
|View full text |Cite
|
Sign up to set email alerts
|

The density and distribution of endothelin 1 and endothelin receptor subtypes in normal and diabetic rat corpus cavernosum

Abstract: ET-1 and ETA receptor binding is increased in diabetic rat cavernosal tissue. A reduction in receptor linked nitric oxide (NO) release has previously been reported in diabetic rats. This finding may provide an explanation for the upregulation of ET-1 and ETA receptor binding in the diabetic rat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 19 publications
4
41
0
3
Order By: Relevance
“…In the diabetic rat study referenced above, the authors were unable to detect any appreciable binding to the ETB receptor in CCSM from either normal or diabetic rats, 19 while the above rabbit study found a three-fold increase in ETB radioligand binding. 20 Recent pharmacologic evidence is consistent with the existence of two different populations of ETB receptors, activation of one causing smooth muscle relaxation (ETB1) and the other causing smooth muscle contraction (ETB2).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In the diabetic rat study referenced above, the authors were unable to detect any appreciable binding to the ETB receptor in CCSM from either normal or diabetic rats, 19 while the above rabbit study found a three-fold increase in ETB radioligand binding. 20 Recent pharmacologic evidence is consistent with the existence of two different populations of ETB receptors, activation of one causing smooth muscle relaxation (ETB1) and the other causing smooth muscle contraction (ETB2).…”
Section: Discussionmentioning
confidence: 83%
“…19 Using the same technique, this same group reported that ETB, but not ETA or ET-1, was significantly upregulated in diabetic rabbits. 20 In a separate study, they reported a decrease in ETB receptor binding sites in the cavernosal tissue of hypercholesterolemic rabbits.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…15,35 Additionally, increased plasma and corporal body endothelin levels have been seen in diabetic men with ED. 36,37 This appears to be important in the pathogenesis of ED, as ET-1 is a key factor in maintaining corpus cavernosal smooth muscle tone. 38,39 While not completely defined, manifestations of endothelial dysfunction may differ between type I and II DM.…”
Section: Diabetes Mellitusmentioning
confidence: 99%
“…4 In the penis, ET-1 is a profibrotic peptide and the most potent stimulator of cavernosal contractility, acting on receptors identified in different animal species, including humans. [3][4][5][6][7][8][9] In human penile cells, ET-1 expression is upregulated by several factors such as transforming growth factor-b1 (TGF-b1), interleukin-1a, ET-1 itself and by prolonged (24 h) hypoxia. 4 Hypoxia is a normal, physiological event in the penis, which, in the flaccid state, resides at a very low oxygen tension (P O 2 ¼ 25-40 mm Hg).…”
Section: Introductionmentioning
confidence: 99%